Multivariable operator theory : a Joint Summer Research Conference on Multivariable Operator Theory, July 10-18, 1993, University of Washington, Seattle - Curto, Raúl E.; Joint Summer Research Conference on Multivariable Operator Theory (Contemporary mathematics, 1995)
This volume contains a collection of papers presented at the Summer Research Conference on Multivariable Operator Theory, held in July 1993 at the University of Washington in Seattle. The articles contain contributions to a variety of areas and topics which may be viewed as forming an emerging new subject. This subject involves the study of geometric rather than topological invariants associated with the general theme of operator theory in several variables. Developments have occurred in several different directions, with the aid of a variety of techniques, and many advances have been made through cross-pollination among different areas of mathematics. The goal of the conference, and of this volume, is to spur discussion of the connections among the various approaches and new directions for research.